Training Nurses in Developing Self-regulation Skills and Its Benefit on Patients' Satisfaction - Kalavana, Theano (My University, 2012)
This was a longitudinal study aimed to examine Self-Regulation skills of nurses (N¼ 338,X¼38.8, SD¼ 8.8) in the clinical setting and their relation to (professional) goal accomplishment and patients’ satisfaction (control group), to develop a 6-month (72 hours)intervention program in which nurses were taught and exercised self-regulation skills (experimental group) and examine the differences between control group and experimental group on SR skills, professional goal accomplishment and patients’ satisfaction.
Keywords: Public; Environmental & Occupational Health; Psychology